(untitled) - Elham Keramati; Yekta Rezazadeh; Fatemeh Ehsani; Majid Mirmohammadkhani; Mohades Paknazar; Mina Sadat Mirshoja (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Due to the decline in population growth in recent years, the government has developed a series of incentive policies aimed at encouraging childbirth and fertility. This study investigates the impact of educating married female students about these governmental incentive policies on their knowledge, attitudes toward childbearing, and fertility motivation. Materials and methods: This study employed a quasi-experimental design utilizing a pre-test–post-test structure with experimental and control groups. The sample comprised 60 married female university students with a mean age of 24.76 years (SD= 3.75). The statistical population included students from Farhangian University and Semnan University of Medical Sciences. All participants completed online questionnaires one session before and one session after the intervention. The questionnaires included: personal demographic data, Miller’s Fertility Motivation Scale, a survey assessing attitudes toward governmental incentives, and a general knowledge test on the state's fertility-related policies. The educational sessions were delivered online via Google Meet over the course of one month, comprising eight group sessions held twice weekly. The control group received no educational intervention during this period. To compare the mean scores between the two groups, paired-sample t-tests and independent-sample t-tests were conducted using SPSS version 24. Results: The results indicated a significant difference in the experimental group before and after the intervention in the variables of positive and negative fertility motivations and attitudes toward government incentives (P<0.05). Additionally, there was a significant difference between the experimental and control groups in the variables of positive and negative fertility motivations and attitudes toward government incentives after the intervention (P<0.05). No significant difference was observed in participants’ general knowledge about government incentive policies (P> 0.05). Conclusion: The results suggest that educational interventions focusing on governmental fertility incentives can effectively improve women’s attitudes by increasing awareness, reshaping perceptions, and potentially enhancing their willingness to pursue childbearing